A mobile application of augmented reality for periodic table with speech recognition - Sen, Tan Chee; Noorlin, Mohd Ali (2021)
A periodic table of elements is a group of various elements arranged according to their various chemical properties which can provides some valuable information. Augmented Reality can play a role in making the learning process more interesting by providing some visualization and interaction with the periodic table.